1981
DOI: 10.7326/0003-4819-94-3-349
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin-Induced Methadone Withdrawal

Abstract: Methadone-maintained volunteers experienced moderately severe opiate withdrawal symptoms within 3 or 4 days of beginning phenytoin in therapeutic doses. The area under the methadone plasma concentration-time curve decreased while the ratio of the pyrrolidine-to-metabolite excretion in urine to this area increased significantly. This suggests that phenytoin accelerates methadone metabolism. Methadone dosing adjustments should be anticipated when phenytoin is initiated or discontinued in methadone-maintained pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(29 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…A unique type of potential problems with LAAM could result from the fact that LAAM depends for its long-acting properties upon successive biotransformations to the other biologically active and long-acting opioid metabolites , norLAAM and dinorLAAM. In the setting of use of a medication which may enhance the hepatic P450 related enzyme systems such as rifampin, phenytoin, phenobarbital, or carbamazepine, or following the chronic use of alcohol, an accelerated biotransformaiton may be seen, as has been documented with respect to methadone (KREEK et al 1976a,b;KREEK 1990a;TONG et al 1981). This could lead to rapid production of the active metabolites.…”
Section: L-a-acetylmethadol (Laam)mentioning
confidence: 90%
See 2 more Smart Citations
“…A unique type of potential problems with LAAM could result from the fact that LAAM depends for its long-acting properties upon successive biotransformations to the other biologically active and long-acting opioid metabolites , norLAAM and dinorLAAM. In the setting of use of a medication which may enhance the hepatic P450 related enzyme systems such as rifampin, phenytoin, phenobarbital, or carbamazepine, or following the chronic use of alcohol, an accelerated biotransformaiton may be seen, as has been documented with respect to methadone (KREEK et al 1976a,b;KREEK 1990a;TONG et al 1981). This could lead to rapid production of the active metabolites.…”
Section: L-a-acetylmethadol (Laam)mentioning
confidence: 90%
“…These studies have been subsequently corroborated by other research groups. A second related observation was made and studied with respect to the effects of phenytoin, a very commonly used anticonvulsant (Dilantin;FINELLI 1976;TONG et al 1981). It was seen that patients who were receiving phenytoin seemed to experience early abstinence symptoms during methadone maintenance treatment.…”
Section: Drug and Alcohol Interactions With Methadonementioning
confidence: 99%
See 1 more Smart Citation
“…The concomitant administration of enzyme inducing (or inhibiting) drugs is known to significantly alter plasma methadone concentrations. Reports have shown that rifampicin [77], phenytoin [78], barbiturates [79] and disulfiram [80] are associated with low plasma methadone concentrations and, if sustained, precipitate opiate withdrawal symptoms. Similar effects have been reported with zidovudine (azidothymidine) [81] as well as fucidic acid and amitriptyline which are not known enyzme inducers.…”
Section: Indications For Plasma Methadone Monitoringmentioning
confidence: 99%
“…One case report described a methadone-maintenance patient who developed signs and symptoms of methadone withdrawal after only a few days of phenytoin therapy (Finelli 1976). A study examining the effects of phenytoin (300 mg/day) on the pharmacokinetics and pharmacological action of methadone was performed in 5 male volunteers enrolled in a methadone-maintenance program (Tong et al 1981). By the third or fourth day after commencement of phenytoin, all 5 individuals experienced moderately severe opiate withdrawal symptoms accompanied by a greater than 50% decrease in methadone trough plasma concentrations from 0.31 to 0.13 j.LmoljL (0.108 to 0.045 j.Lg/ml) and a decreased urinary methadone-to-pyrrolidine metabolite excretion ratio (0.80 to 0.11).…”
Section: Phenytoinmentioning
confidence: 99%